2018
DOI: 10.20409/berj.2018.106
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment, International Trade and Financial Development in BRICS-T Countries: A Bootstrap Panel Causality Analysis

Abstract: The aim of this paper is to investigate, within a Bootstrap panel causality approach, the interactions among foreign direct investment (FDI), international trade and financial development in BRICS-T countries (Brazil, Russia, India, China South Africa and Turkey)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, there is single track causality between the progress of the financial sector and the inflow of foreign direct investment, and its impact is significant [11]. Through the research on studied the interaction between FDI, national trade and financial progress in the BRIC countries (Russia, China, Brazil, India, South Africa, and Turkey), Sahin concluded that FDI promotes financial progress in Brazil, Russia and China and there is no causal relationship between FDI and financial development in India, South Africa, and Turkey, but financial development promotes FDI in these countries [12]. Based on India's FDI and financial development data from 1980 to 2017, Mishra found that the progress of India's financial sector (especially the banking industry and capital market) has played an important role in attracting FDI, and the substantial growth of FDI will have a significant positive impact on economic growth [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is single track causality between the progress of the financial sector and the inflow of foreign direct investment, and its impact is significant [11]. Through the research on studied the interaction between FDI, national trade and financial progress in the BRIC countries (Russia, China, Brazil, India, South Africa, and Turkey), Sahin concluded that FDI promotes financial progress in Brazil, Russia and China and there is no causal relationship between FDI and financial development in India, South Africa, and Turkey, but financial development promotes FDI in these countries [12]. Based on India's FDI and financial development data from 1980 to 2017, Mishra found that the progress of India's financial sector (especially the banking industry and capital market) has played an important role in attracting FDI, and the substantial growth of FDI will have a significant positive impact on economic growth [13].…”
Section: Literature Reviewmentioning
confidence: 99%